Indications for Keratoplasty in King Abdul-Aziz University Hospital: Five Years of Experience - Alqahtani, Saeed Saleh (Malaysian Journal of Medical Sciences, 2025)
Background: This study aimed to describe the indications and surgical techniques for corneal transplantation performed at a tertiary hospital over the past five years. Methods: A retrospective cross-sectional chart review was conducted of medical records for keratoplasty cases admitted to the hospital during this period. For each patient, data were collected on demographic characteristics, clinical indications for keratoplasty, associated ocular conditions, the surgical technique used, graft size, postoperative outcomes, suture removal time, and complication rates. Results: A total of 132 patients (159 keratoplasties) were included. The leading indications for keratoplasty were keratoconus (74/159, 46.5%), corneal decompensation including pseudophakic bullous keratopathy (37/159, 23.3%), and microbial keratitis (10/159, 6.3%). Penetrating keratoplasty (PKP) was the most commonly performed surgical technique (84/159, 53%), followed by Descemet’s stripping automated endothelial keratoplasty (DSAEK, 35/159, 22%). Postoperatively, mean intraocular pressure remained stable (approximately 16–17 mmHg) throughout follow-up visits. By two months, corneal clarity was achieved in nearly 90% of cases, with gradual improvement in visual acuity up to three months. Conclusions: The findings highlight key indications and evolving surgical techniques in corneal transplantation, underscoring the importance of early diagnosis and adoption of less invasive procedures to improve patient outcomes. These insights support targeted clinical strategies and resource planning to optimise corneal transplant care.